2015
DOI: 10.1049/mnl.2014.0631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminium doping amount on the electrochemical properties of ZnO nanoparticles as anode for lithium ion batteries

Abstract: Aluminium (Al)-doped ZnO nanoparticles (NPs) have been synthesised by a simple solvothermal method at low temperature. The electrochemical properties of the obtained products as anode for lithium ion batteries were examined through galvanostatic dischargecharge, cyclic voltammetry and electrochemical impedance spectroscopy measurements. The results show that the reversible capacities of Al-doped ZnO NPs are higher than the capacities of pure ZnO synthesised under the same experimental conditions. ZnO NPs doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…4 c shows the CV curves of the ZnO nanoparticles acquired at 700°C at scanning rate of 0.1 mV s −1 . During the first scan, there is one strong reduction peak at 0.26 V, which is related to the reduction of ZnO, the formation of lithium‐zinc alloy and the growth of SEI layer [5, 12, 25]. In the corresponding anodic scan, four oxidation peaks appeared at 0.28, 0.35, 0.52 and 0.67 V, which correspond to the multi‐step dealloying process of lithium‐zinc alloy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 c shows the CV curves of the ZnO nanoparticles acquired at 700°C at scanning rate of 0.1 mV s −1 . During the first scan, there is one strong reduction peak at 0.26 V, which is related to the reduction of ZnO, the formation of lithium‐zinc alloy and the growth of SEI layer [5, 12, 25]. In the corresponding anodic scan, four oxidation peaks appeared at 0.28, 0.35, 0.52 and 0.67 V, which correspond to the multi‐step dealloying process of lithium‐zinc alloy.…”
Section: Resultsmentioning
confidence: 99%
“…Introduction: Zinc oxide (ZnO) has been attracted much attention as a promising anode material for lithium ion batteries (LIBs) due to its low-cost, environmental benignity and high theoretical capacity of 987.7 mAh g −1 [1], while its drawbacks including low electrical conductivity and strong volume variation constantly affect their applications in LIBs [2,3]. To overcome the problems, the electrochemical properties of ZnO could be improved by incorporating carbon materials [4] or doping with hetero-elements [5,6]. In addition, another important strategy is fabricating nanostructured ZnO with especial morphology, such as nanorods [7,8], nanosheets [9], nanospheres [10], nanotubes [11] as well as mesoporous ZnO [12], which could effectively improve the lithium intercalating activity and cycling stability of the electrode materials.…”
mentioning
confidence: 99%
“…al, [24] also discussed that increased the doping leads to decreased the conductivity which is probably due to the deformation of ZnO lattices and the limitation of electron transport.…”
Section: A Electrical Propertiesmentioning
confidence: 99%
“…Zhang et al reported that Aluminum (Al)-doped zinc oxide (ZnO) nanoparticles, particularly those with a 2% molar ratio of Al, exhibited superior reversible capacities compared to undoped ZnO under the same experimental conditions [11].…”
Section: Introductionmentioning
confidence: 99%